Effect of running speed on knee biomechanics in collegiate athletes following anterior cruciate ligament reconstruction - Knurr, K. A.; Cobian, D. G.; Kliethermes, S. A.; Joachim, M. R.; Heiderscheit, B. C. (Medicine & Science in Sports & Exercise, 2024)
Introduction Athletes post-anterior cruciate ligament reconstruction (ACLR) demonstrate altered surgical knee running kinematics and kinetics compared to the non-surgical limb and healthy controls. The effect of running speed on biomechanics has not been formally assessed in athletes post-ACLR. The purpose of this study was to characterize how knee biomechanics change with running speed between 3.5-7 (EARLY) and 8-13 (LATE) months post-ACLR.